Bacteria of enclosed abscesses - Otto, Henry; Spohr, George A. (My University, 1906)
Introduction: The purpose of this thesis is to find the micro-organisms which cause suppuration in enclosed abscesses. In working with abscesses before they were opened to the action of the surrounding atmosphere, the object was to eliminate contamination by external organisms that would interfere very markedly and thus prevent the true conclusions from being reached and in obtaining the best results. The material used in this experiment was procured from abscesses on several different horses which were being treated here at the K. S. A. C. Veterinary Hospital. Two of the cases were Fistulus Withers, two Poll Evil, while the fifth was taken from a large abscess situated on the abdomen. The following method of extracting the material without subjecting it to external contamination, was employed. In each case the hair was shaved off from about the abscess and the skin then thoroughly disinfected. It was, however, first thoroughly washed with soap and water and then alcohol was applied for ten minutes. After this operation the skin was again washed with corrosive sublimate for another ten minutes and then one of the coal tar products was applied. A hypodermic needle and syringe was previously disinfected with a 5% carbolic acid solution for fifteen minutes and after being thoroughly washed with sterilized water the needle was plunged into the abscess and a small quantity of the pus removed by means of the syringe. All of our pus was gathered in this way, securing it without its becoming contaminated by the air.
Citation: Otto, Henry and Spohr, George A. Bacteria of enclosed abscesses. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Veterinary Medicine; Abscesses; Equine; Microbiology; Theses